An Adolescent Presented With Hemoptysis: Pulmonary Artery Aneurysm in Pediatric Behçet’s Disease - Nilay BAŞ İKİZOĞLU,; Emine ATAĞ,; Almala Pınar ERGENEKON,; Cansu YILMAZ YEĞİT,; Yasemin GÖKDEMİR,; Ela ERDEM ERALP,; Ayşim BÜGE ÖZ,; Bulent KARADAG, (Archives of Rheumatology, 2020)
Behçet’s disease (BD) is a rare autoimmune and chronic inflammatory vasculitis, characterized by relapsing episodes of oral aphthous and genital ulcers, skin lesions, ocular lesions and vascular involvement. Pulmonary artery involvement is rare in BD but it carries a high mortality risk. In this article, we report a 15-year-old male patient presented with a two-month history of hemoptysis, cough, fewer and weight loss. On physical examination, auscultation revealed decreased breath sounds at left lung base. Bronchoscopy showed narrowed left lower lobe bronchus due to the external compression. Computed tomography angiography revealed multiple bilateral pulmonary artery aneurysms. Pathergy test was positive and he was diagnosed with BD. BD should be considered in the differential diagnosis of childhood hemoptysis.